2017
DOI: 10.1158/1078-0432.ccr-16-1040
|View full text |Cite
|
Sign up to set email alerts
|

PARP Inhibitor Activity Correlates with SLFN11 Expression and Demonstrates Synergy with Temozolomide in Small Cell Lung Cancer

Abstract: Purpose PARP inhibitors (PARPi) are a novel class of small molecule therapeutics for small cell lung cancer (SCLC). Identification of predictors of response would advance our understanding, and guide clinical application, of this therapeutic strategy. Experimental Design Efficacy of PARP inhibitors olaparib, rucaparib, and veliparib, as well as etoposide and cisplatin in SCLC cell lines, and gene expression correlates, were analyzed using public datasets. HRD genomic scar scores were calculated from Affymetr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
243
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 266 publications
(265 citation statements)
references
References 49 publications
(73 reference statements)
9
243
3
Order By: Relevance
“…As already indicated, SCLC exhibits high levels of PARP1 expression and there are preclinical data to support PARP1 inhibition for clinical evaluation as a monotherapy and in combination with DNA damaging agents [36,41,42]. In tumour models PARP inhibitors synergise with agents that increase the prevalence of SSBs such as temozolomide [43,44]. In addition, in preclinical SCLC xenografts Byers et al demonstrated single agent activity of olaparib, which was further increased when combined with cisplatin and etoposide or irinotecan [45].…”
Section: Parp Inhibitorsmentioning
confidence: 94%
See 4 more Smart Citations
“…As already indicated, SCLC exhibits high levels of PARP1 expression and there are preclinical data to support PARP1 inhibition for clinical evaluation as a monotherapy and in combination with DNA damaging agents [36,41,42]. In tumour models PARP inhibitors synergise with agents that increase the prevalence of SSBs such as temozolomide [43,44]. In addition, in preclinical SCLC xenografts Byers et al demonstrated single agent activity of olaparib, which was further increased when combined with cisplatin and etoposide or irinotecan [45].…”
Section: Parp Inhibitorsmentioning
confidence: 94%
“…Olaparib is the most extensively investigated PARPi and is approved by the US FDA for use in pretreated advanced germline BRCA mutated ovarian cancer [40]. As already indicated, SCLC exhibits high levels of PARP1 expression and there are preclinical data to support PARP1 inhibition for clinical evaluation as a monotherapy and in combination with DNA damaging agents [36,41,42]. In tumour models PARP inhibitors synergise with agents that increase the prevalence of SSBs such as temozolomide [43,44].…”
Section: Parp Inhibitorsmentioning
confidence: 99%
See 3 more Smart Citations